Examining the Influence of COVID-19 on PCOS Symptoms and the Role of Homeopathy in their Alleviation (Homoeopathy for All, 2023)
Polycystic ovarian syndrome (PCOS)  is a prevalent endocrine disorder  affecting reproductive-aged women  worldwide, characterized by hormonal  imbalances, irregular menstrual cycles,  ovarian cysts, and various metabolic  disturbances, hyperandrogenism,  ovulatory dysfunction, and polycystic  ovarian morphology.1 Over the past  couple of years, the world has been  grappling with the devastating effects  of the COVID-19 pandemic caused  by the novel coronavirus, SARS CoV-2. While the primary impact of  COVID-19 is respiratory, emerging  evidence suggests that the virus can  have wide-ranging effects on other  organ systems, including the endocrine  system. When we examine its effects  on the female endocrine system, it  results in menstrual irregularities,  hormonal imbalances, fertility  issues, etc. Apart from its direct  effects, even the use of COVID-19  vaccine is also reported to influence  the menstrual cycle length, flow,  duration of menstruation, symptoms,  and abnormal bleeding without an  effect on post-menopausal vaginal  bleeding.2 All these may possibly end  up in PCOS due to multiple factors,  including hormonal imbalance, stress,  and others. Researchers have also  traced its possible mechanism to be  related to the increased androgen  activity, which make the body  vulnerable to infections.
Keywords: COVID-19; metabolic; mechanism